A Comparative Studyof Construction Sequence with Conventional Analysis - Darshan G. Gaidhankar, Yash V. Pitamberwale, Mrudula S. Kulkarni, Sumant N. Shinde, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Rising incidents of failure of buildings during the construction phase is an increasing concern in India. The failure of structural elements like slabs, beams, columns, and shear walls is critical. Construction sequence analysis (CSA) helps in analysing the building in a staged fashion. Despite its importance, our knowledge of CSA is poor, and the implementation is imperfect. The purpose of this study is to investigate the change in values of numerous structural parameters namely axial force, shear force, and bending moment during and after construction. Using CSA, this study analysed the values of structural parameters of a 15 storied building located in Pune and measured these results against the dynamic analysis of the building. The values of deflection and shear forces found in CSA are up to 45% more than dynamic analysis. This study definitively answers the question regarding the failure of buildings during the construction phase and how it can be avoided by using CSA. Experimental studies are needed to establish real-world values of structural parameters.